2018
DOI: 10.1159/000487029
|View full text |Cite
|
Sign up to set email alerts
|

Α-Melanocyte-Stimulating Hormone Protects Early Diabetic Retina from Blood-Retinal Barrier Breakdown and Vascular Leakage via MC4R

Abstract: Background/Aims: Blood-retinal barrier (BRB) breakdown and vascular leakage is the leading cause of blindness of diabetic retinopathy (DR). Hyperglycemia-induced oxidative stress and inflammation are primary pathogenic factors of this severe DR complication. An effective interventional modality against the pathogenic factors during early DR is needed to curb BRB breakdown and vascular leakage. This study sought to examine the protective effects of α-Melanocyte-stimulating hormone (α-MSH) on early diabetic reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…To assess BBB integrity after mild I/R (20 min / 4 h) injury, we monitored the extravasation of Evans blue (EB) dye into the brain parenchyma after injection into the mouse tail vein. Similar to previous reports, 34‐36 we observed more severe brain leakage of EB after ischemic stroke in the ipsilateral brain tissues of HG mice, compared to NG controls (Figure 1A,B). To further quantitatively evaluate the extent of EB leakage, fluorescence intensity was used to measure the EB absorbance at 620 nm.…”
Section: Resultssupporting
confidence: 92%
“…To assess BBB integrity after mild I/R (20 min / 4 h) injury, we monitored the extravasation of Evans blue (EB) dye into the brain parenchyma after injection into the mouse tail vein. Similar to previous reports, 34‐36 we observed more severe brain leakage of EB after ischemic stroke in the ipsilateral brain tissues of HG mice, compared to NG controls (Figure 1A,B). To further quantitatively evaluate the extent of EB leakage, fluorescence intensity was used to measure the EB absorbance at 620 nm.…”
Section: Resultssupporting
confidence: 92%
“…Other studies have demonstrated protective, anti-inflammatory, and anti-apoptotic effects of α-MSH in the retina in rat models of diabetic retinopathy (Zhang et al, 2014; Cai et al, 2018). Potential protective mechanisms of α-MSH against diabetic retinopathy suggested by these studies include inhibition of Forkhead box O genes induced by high glucose concentrations (Zhang et al, 2014) and the correction of aberrant expression of inflammatory factors and tight junction genes, and inhibition of hyperpermeability, in diseased retinas (Cai et al, 2018). Investigation of whether PL-8177 and/or PL-8331 possess similar mechanisms and protective effects in preclinical models of diabetic retinopathy is of interest for future studies.…”
Section: Discussionmentioning
confidence: 93%
“…To investigate whether micro-and macroaneurysms in the hyperglycemic rat retinas (observed using OCT) reflect sites of vessel leak, rats were perfused at the age of 3 months with Evans Blue dye as previously described [33]. Briefly, Evans Blue dye (30 mg/ml; Sigma-Aldrich, USA) was dissolved in normal saline and filtered.…”
Section: Evans Blue Dye Assessment Of Vessel Leakmentioning
confidence: 99%